Spatial Distribution and Source Apportionment of Heavy Metals in the Topsoil of Weifang City, East China - Li, Yan; Xu, Zhiqiang; Ren, Hanhan; Wang, Dong; Wang, Jian; Wu, Zhen; Cai, Pengjie (Frontiers in Environmental Science, 2022)
The distribution of heavy metals in topsoil can significantly impact human health. A total of 1556 samples were collected from the topsoil of Weifang City, China. Various indices, including the pollution index (PI), the Nemerow integrated pollution index (PN), and the potential ecological risk index (RI), were used to analyse the heavy metal pollution levels. The sources of heavy metals were analysed using the positive matrix factorization (PMF) model. The results showed that the ecological risk level of Cu, Pb, Zn, Ni, Cr, and As in the study area is relatively safe, but the ecological risk level of Cd and Hg is relatively high, leading to an increase in the ecological risk level of heavy metals in the study area. Six main sources of the eight heavy metals were identified by PMF, including oil parent material and nonferrous metal industrial sources with Cr and Ni as main loads, fossil fuel (coal)-related industrial sources with As, diesel fuel-related sources with Cu, gasoline transportation sources with Pb, pesticides sources with Hg, organic fertilizers sources with Cd and Zn.